Review of the role of gut microbiota in mass rearing of the olive fruit fly, Bactrocera oleae, and its parasitoids. Issue 3 (19th September 2017) - Ras, Erica; Beukeboom, Leo W.; Cáceres, Carlos; Bourtzis, Kostas
Abstract: The olive fruit fly, Bactrocera oleae (Rossi) (Diptera: Tephritidae), is the major insect pest in commercial olive ( Olea europaea L., Oleaceae) production worldwide. Its population management is largely based on the use of insecticides. However, concerns about the impact of insecticides on the environment and human health along with increasing resistance development calls for novel and environment‐friendly approaches for population management. Integrated pest management programmes with a sterile insect technique (SIT) component and parasitoids are currently considered for the control of B. oleae . A major challenge for the development of such tools is mass rearing of both host and parasitoids. In this review, we consider the role of endogenous microbiota and its potential exploitation for improving the efficacy, quality, and cost effectiveness of mass rearing B. oleae as well as their parasitoids.